Coral reefs fisheries development business strategy in Sabang City. Issue 1 (November 2021) - Agustina, I; Aprilia, R M; Salmarika, S; Rahayu, R; Arif, M; Rizwan, T
Abstract: Marine fisheries are an important source of food and income for people all over the world. Billions of people, most of them from developing countries, rely on fish as a major source of animal protein. Fisheries play an important role in the prevention and reduction of poverty. Fisheries provide nets that are essential to people when other work resources are unavailable. The aim of this study is the strategy for developing coral fisheries in Sabang city. The method used in research is to use the SWOT method of analysis. Fisheries development strategy in Sabang city: 1). Develop cathing tool technology to replace the previous cathing tools that are non-environmentally friendly. 2). Conducting the coral reef conservation socialization where the coral fish live. 3). Cooperating with the society in controlling fishing areas by utilizing the local culture that is still very strong in protecting the sea to avoid illegal and excessive exploitation of fish. 4). Means of transportation and distribution for the export of coral fish, which results in a high selling price. 5. The development of the added value of coral fishery products for the welfare of fishermen.